Geothermal Fluid Characterisics based on Geochemical Analysis of Hot Water in The Wawolesea Area, North Konawe Regency Southeast Sulawesi Province: Karakteristik Fluida Panas Bumi Berdasarkan Analisis Geokimia Air Panas Daerah Wawolesea Kabupaten Konawe Utara Sulawesi Tenggara - Rizky Nurul Aulia; Irzal Nur; Asran Ilyas (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2022)
North Konawe Regency is an area with interesting geothermal potential to be studied. The observed geothermal potential manifestation is located in the Wawolesea area through the collection and analysis of three hot spring samples. This study aims to determine the characteristics of geothermal fluids, namely the type and origin of the fluid by conducting geochemical analysis on samples of hot springs in the study area which further shows the content of elements and chemical compounds and their respective concentrations. The analysis in this research is Inductively Coupled Plasma-Atomic Emission Spectroscopy (ICP-AES) to obtain B and Li concentrations, conductivity meter to obtain Cl concentration, visible spectroscopy method for SO4 concentration and HCO3 concentration measured by acid-base titration. The results showed that the type of hot springs in the study area was included in the Chloride type with a percentage of 81.8156%-83.3976% with a pH value of 6.7-7.4 and a hot spring temperature of 50-54°C then plotted into trilinear diagram. The Cl-Li-B Ternanry diagram shows that the source of the fluid is in a reservoir that has the same rock structure and comes from the old hydrothermal system. Based on the results of the analysis of fluid characteristics obtained from the research, it can be concluded that the hot springs of the Wawolesea Region are an indicator of the presence of geothermal sources and further research is needed on the magnitude of the geothermal potential.